The efficacy of angiotensin converting enzyme inhibitors versus angiotensin II receptor blockers on insulin resistance in hypertensive patients: A protocol for a systematic review and meta-analysis - Yao, Jia (Medicine (Baltimore), 2020)
BACKGROUND: Previous studies have shown inconsistent outcomes in the efficacy of angiotensin-converting enzyme inhibitors (ACE inhibitors) and angiotensin receptor blockers (ARBs) on insulin resistance (IR). Hence, we aim to compare the efficacy of ACE inhibitors with ARBs on IR in hypertensive patients. METHODS: Five electronic databases (included The Cochrane Library, MEDLINE, Embase, Web of Science, and Cochrane Central Register of Controlled Trials) will be searched. Randomized controlled trials (RCTs) will be included if they recruited hypertensive participants for assessing the effect of ACE inhibitors on IR versus ARBs. The primary outcome will be IR (using recognized methods such as homeostasis model assessment of insulin resistance), secondary outcomes will be blood pressure, fasting plasma glucose, fasting plasma insulin. Relevant literature search, data extraction, and quality assessment will be performed by 2 researchers independently, and the third researcher will be involved in a discussion for any disagreements. All analyses will be performed based on the Cochrane Handbook for Systematic Reviews of Interventions. Stata 12.0 software will be used for statistical analysis. The effect size of dichotomous data will be measured using the odds ratio (OR), and the effect size of continuous data will be measured using the standardized mean difference. And 95% confidence intervals will be calculated. Heterogeneity will be tested by χ(2)-based Cochran Q statistic and I(2) statistic. Sensitivity analysis and subgroup analysis will be used to observe changes in the pooled effect size and heterogeneity between included studies, to assess the reliability and stability of the pooled results. The funnel plot and Egger's and Begg's tests will be used to judge publication bias, and the trim and fill method will be used to correct the funnel asymmetry caused by publication bias. P < 0.05 will be considered to indicate a statistically significant result. RESULTS: This systematic review and meta-analysis will assess the efficacy of ACE inhibitors versus ARBs on IR in hypertensive patients. CONCLUSIONS: Our study will show the efficacy of ACE inhibitors versus ARBs on IR in hypertensive patients. And it may find a more beneficial therapeutic option to assist clinicians in making clinical decisions. ETHICS AND DISSEMINATION: This study is a protocol for systematic review and meta-analysis of the efficacy of ACE inhibitors and ARBs on IR in hypertensive patients. This systematic review and meta-analysis will be published in a journal and disseminated in print by peer-review. INPLASY REGISTRATION NUMBER: INPLASY202050032.